Pengaruh Beban Kerja, Lingkungan Kerja, dan Kepuasan Kerja terhadap Turnover Intention di PT. X - Silvia Anastasia; Kriswanto Widiawan (Jurnal Titra, 2023)
Company X is a company engaged in the field of logistics. The turnover intention at this company is categorized as high, particularly within the Freight Clearance Project Cargo (FCPC) and Strategic Procurement (SP) departments with a turnover percentage of 13% in the last three years. The objective of this research is to identify the factors influencing turnover intention,specifically focusing on workload, work environment, and work satisfaction. The research was conducted with the method of distributing questionnaires on a Likert scale of 1-5 and data processing using Partial Least Squares (PLS) model evaluation using SmartPLS 3.0. Descriptively, the lowest mean in the FCPC department is found in the complexity of work, noise in the workplace,and wages given. The lowest mean in the SP department is found in the deadline to achieve the target, noise in the workplace, and wages given. These indicators need to be further reviewed by the company. The hypothesis results indicate that workload, work environment, and work satisfaction have no impact on the turnover intention level. It’s known that the variables of workload, workenvironment, and job satisfaction have an influence of 20.2% on turnover intention. Therefore, there are still other variables impacting turnover intention.